Comparison of alfaxalone-medetomidine and tiletamine-zolazepam in rescued common palm civets (Paradoxurus musangus) - Ahmad, Ali Anwar; Abd Wahab, Norsham; Yeo, Wenjing Clara; Yin, Serena Jocelyn Oh Wai; Chen, Hui Cheng (Japanese Society of Veterinary Science, 2019)
Forty rescued common palm civets were anesthetized. Twenty animals received intramuscular injections of alfaxalone 5 mg/kg and medetomidine 0.05 mg/kg (A-M group), whereas twenty animals received 5 mg/kg of tiletamine and zolazepam (T-Z group). The A-M group was reversed with atipamazole 0.25 mg/kg. There were no significant differences in the time from anesthetic injection to induction and intubation between the A-M and T-Z groups. The time from the injection of reversal in the A-M group and the time from cessation of isoflurane in the T-Z group to extubation, first response to recovery and ambulation were longer (P<0.05) in the T-Z group. The T-Z group recorded lower (P<0.05) rectal temperatures compared to the A-M group. This study showed that both drug combinations can be used effectively for the immobilization of civets. The A-M combination provided better anesthetic depth, but with higher incidence of bradycardia and hypoxemia. The recovery time was reduced significantly as atipamezole was used as a reversal agent in the A-M combination.